Economic valuation of cultural ecosystem services provided by small-scale European Atlantic fisheries - Juan José García-del-Hoyo; David Castilla-Espino; Arantza Murillas Maza; Laura García-de-la-Fuente; Richard Curtin; Angela Muench; Inês Sousa (Fisheries Research, 2026)

An evidence base of ecosystems services provided by diadromous fish in the European Atlantic Area - Matthew Ashley; Arantza Murillas; Angela Muench; Cristina Marta-Pedroso; Lynda Rodwell; Sian Rees; Emma Rendle; Tea Bašić; Gordon H. Copp; Estibaliz Díaz; David J. Nachón; Patrick Lambert; et al. (Ecosystem Services, 2023)

Assessing the welfare impacts of changes in recreational fisheries management: A modelling approach for European sea bass - Fabio Cevenini; Barnaby Andrews; Angela Muench; Philip Lamb; Silvia Ferrini; Kieran Hyder (Marine Policy, 2023)

An Assessment of Economic Viability of the Ascension Island Tuna Longline Fishery Management: Implications for Marine Protected Area Planning and Future Fisheries Management - Angela Muench; Elena Mengo; Sam Weber; Diane Baum; Andrew James Richardson; Hannah Thomas; Paul Whomersley (Frontiers in Marine Science, 2022)
The designation of large scale marine protected areas (MPAs) has increased in recent years to address global issues such as biodiversity loss and the conservation of vulnerable marine habitats. While designing a large scale MPAs in the Exclusive Economic Zone (EEZ) of Ascension Island, the monitoring and enforcement costs were estimated for the two options under consideration: partial closure or full closure of the EEZ for the international commercial fleet. It was found that number of licenses to be sold to the international fleet to allow them access to the EEZ of Ascension Island would need to be increased to fund the monitoring and enforcement cost in case of a partial closure of the EEZ of Ascension Island. In this study, the future economic viability of the licensed big eye tuna fishery was addressed. The study explored economic drivers thought to be linked to license sales. It was shown that cost of licenses had not caused the observed decline in license sales but a shift in consumer demand toward lighter tuna species resulted in a decrease in Japanese imports for bigeye tuna ( Thunnus obesus ). This change in demand led to global changes in fishing effort and a drop in demand for licenses to fish within the Ascension Island EEZ. This study provided a valuable insight into the economic viability of the bigeye tuna fishery within the Ascension Island EEZ which informed the subsequent decision to close the bigeye tuna fishery as part of the designation of an Ascension Island highly protected large-scale MPA.